Differentiation of Benign and Malignant Pathology in the Head and Neck Using 3T Apparent Diffusion Coefficient Values: Early Experience - Srinivasan, A.; Dvorak, R.; Perni, K.; Rohrer, S.; Mukherji, S.K. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: The purpose of this work was to study differences in apparent diffusion coefficient (ADC) values between benign and malignant head and neck lesions at 3T field strength imaging.MATERIALS AND METHODS: Our study population in this retrospective study was derived from the patient population who had undergone routine neck 3T MR imaging (for clinical indications) from December 2005 to December 2006. There were 33 patients identified: 17 with benign and 16 with malignant pathologies. In all of the subjects, conventional MR imaging sequences were performed apart from diffusion-weighted sequences. The mean ADC values in the benign and malignant groups were compared using an unpaired t test with unequal variance with a P < 0.05 considered statistically significant.RESULTS: There was a statistically significant difference (P = .004) between the mean ADC values (in 10−3 mm2/s) in the benign and malignant lesions (1.505 ± 0.487; 95% confidence interval, 1.305–1.706, and 1.071 ± 0.293; 95% confidence interval, 0.864–1.277, respectively). There were 2 malignant lesions with ADC values higher than 1.3 × 10−3 mm2/s and 5 benign lesions with ADC values less than 1.3 × 10−3 mm2/s. The lack of overlap of ADC values within 95% confidence limits suggests that a 3T ADC value of 1.3 × 10−3 mm2/s may be the threshold value for differentiation between benign and malignant head and neck lesions.CONCLUSION: ADC values of benign and malignant neck pathologies are significantly different at 3T imaging, though larger studies are required to establish threshold ADC values that can applied in daily clinical practice.